2008
DOI: 10.1177/155005940803900304
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Inhibition in Motor and Non-Motor Regions: A Combined TMS-EEG Study

Abstract: A number of studies using paired pulse transcranial magnetic stimulation (TMS) have demonstrated that cortical inhibition (CI) of the motor cortex can be recorded and also gauged through surface electromyography. However, recording CI from other brain regions that are more directly related with the pathophysiology of some neurologic and psychiatric disorders (e.g., dorsolateral prefrontal cortex (DLPFC) in schizophrenia) was previously fraught with technical difficulties. This study was therefore designed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…Using TMS-EEG, several studies have shown that LICI is associated with reduced excitability in both motor and nonmotor areas of cortex [23,[39][40][41]. For the primary motor cortex, the magnitude of this inhibition correlates with inhibition of the MEP, demonstrating the involvement of mechanisms comparable to those reflected by conventional LICI measurements.…”
Section: Mechanisms Of Licimentioning
confidence: 97%
“…Using TMS-EEG, several studies have shown that LICI is associated with reduced excitability in both motor and nonmotor areas of cortex [23,[39][40][41]. For the primary motor cortex, the magnitude of this inhibition correlates with inhibition of the MEP, demonstrating the involvement of mechanisms comparable to those reflected by conventional LICI measurements.…”
Section: Mechanisms Of Licimentioning
confidence: 97%
“…However, the ability to noninvasively investigate SICI and ICF in other areas would be highly desirable, for example, in prefrontal areas, which are more directly involved in cognitive disorders (Julkunen et al, 2011). Recent technical advances have enabled the concurrent recording of electroencephalographic (EEG) responses to TMS (Ilmoniemi and Kicic, 2010), thus providing a potentially more direct measure of induced changes in neuronal activity and extending the use of TMS to non-motor areas Fitzgerald et al, 2008). Such studies have demonstrated EEG neurophysiological correlates of cortical inhibitory circuits such as GABA B -mediated longinterval intracortical inhibition (LICI) in motor and dorsolateral prefrontal cortex (DLPFC) Fitzgerald et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalogram (EEG) was recorded through a 64-channel Synamps2 EEG system (Compumedics, Neuroscan, Texas, USA) and concurrently TMS was delivered over the EEG cap according to previously published methods Fitzgerald et al, 2008). Eye movements were recorded using four facial electrodes (above and below the left eye and on the outer canthi of the eyes).…”
Section: Eeg Recording and Analysismentioning
confidence: 99%